A RETROSPECTIVE STUDY OF JAUNDICE IN INFANTS IN KYIV FROM 2017 TO 2021 - Kachalova, Olga; Ipatii, Nataliia; Gnyloskurenko, Ganna; Aliusef, Maiia; Mityuryayeva, Inga; Molochek, Nataliia (Eastern Ukrainian Medical Journal, 2024)
Study objectives. The aim of the study was to evaluate the effectiveness of inpatient medical care in Kyiv (diagnostic capabilities and prescription of phototherapy) for newborns with various clinical forms of jaundice during 2017–2021. Methods. We performed a retrospective analysis of 616 infant jaundice cases of various clinical forms at the Department of Neonatal Pathology at Children’s Clinical Hospital No. 6 in Kyiv (2017–2021), diagnosed as ICD P59 neonatal jaundice (NJ) and prolonged jaundice (PJN) and P55 hemolytic disease of the newborn (HDN) based on the relevant criteria. For statistical analysis, MedStat (v2.6.2) and EZR (v1.61) were used. The analysis showed that hospitalization with various forms of jaundice decreased in 2021 by about 2.1 times vs. 2018 and by 1.5 times vs. 2017 (p < 0.001). PJN was more common (55.0%) than NJ (39.8%) and HDN (5.2%), p < 0.001. A logistic regression model (AUC = 0.785) showed that the manifestation of PJN might be influenced by a history of cesarean section. At the time of hospitalization, there was no significant difference between the bilirubin levels measured by two methods: total serum bilirubin (TSBa) and transcutaneous bilirubin (TcBa), p = 0.380. Children with HDN (84.4%) were more likely to require phototherapy for more than 5 days than children with NJ (63.7%) and PJN (62.2%), p < 0.05. Conclusion. The study showed a decrease in the number of hospitalizations for jaundice in infants from 2017 to 2021. The prevalence of PJN was higher than NJ. A history of cesarean section was associated with PJN. Median bilirubin levels showed no significant difference between the two methods. Children with HDN more often required prolonged phototherapy, which was probably due to a less effective daily decline in bilirubin levels.